2010
DOI: 10.1016/j.cmet.2010.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cells Expressing γ Subunit Variants to Identify Diverse Mechanisms of AMPK Activation

Abstract: SummaryA wide variety of agents activate AMPK, but in many cases the mechanisms remain unclear. We generated isogenic cell lines stably expressing AMPK complexes containing AMP-sensitive (wild-type, WT) or AMP-insensitive (R531G) γ2 variants. Mitochondrial poisons such as oligomycin and dinitrophenol only activated AMPK in WT cells, as did AICAR, 2-deoxyglucose, hydrogen peroxide, metformin, phenformin, galegine, troglitazone, phenobarbital, resveratrol, and berberine. Excluding AICAR, all of these also inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
720
2
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 694 publications
(768 citation statements)
references
References 66 publications
(74 reference statements)
32
720
2
6
Order By: Relevance
“…The following food groups and food extracts have high AMPKactivating capacity: resveratrol (red grape skin extract) [114][115][116][117][118], nootkatone (grapefruit extract) [119], ajoene (garlic extract) [120], BDIM (cruciferous vegetable extract) [19,121], and many others [122]. Medicines activate AMPK including Asa [16], Met [35], phenformin [123,124], rosiglitazone, and phenobarbital [125,126], and there may be others.…”
Section: Discussionmentioning
confidence: 99%
“…The following food groups and food extracts have high AMPKactivating capacity: resveratrol (red grape skin extract) [114][115][116][117][118], nootkatone (grapefruit extract) [119], ajoene (garlic extract) [120], BDIM (cruciferous vegetable extract) [19,121], and many others [122]. Medicines activate AMPK including Asa [16], Met [35], phenformin [123,124], rosiglitazone, and phenobarbital [125,126], and there may be others.…”
Section: Discussionmentioning
confidence: 99%
“…As a structural analogue of PMQ, quercetin was able to inhibit mitochondrial F0F1-ATPase activity and increase the AMP:ATP ratio, further activating AMPK [46]. Another study showed that quercetin activated AMPK by AMP-dependent and AMP-independent mechanisms [47]. Additionally, quercetin has been shown to activate AMPK via activation of reactive oxygen species generation and inositol-requiring enzyme 1α (IRE1α) RNase [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we tested whether short treatments (1-2 h) with AMPK activators can induce an increase in SIRT1 activity without changes in the intracellular levels of NAD ϩ . To test our hypothesis, we used several AMPK activators: A769662 (52), AICAR (53), and oligomycin (54). We found that a short incubation of A549 cells with all these AMPK activators promoted SIRT1 activation (Fig.…”
Section: Resultsmentioning
confidence: 99%